2020
DOI: 10.3390/brainsci10090624
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomical and Functional Heterogeneity of the Mediodorsal Thalamus

Abstract: The mediodorsal nucleus (MD) represents just one piece of a complex relay structure situated within the brain, called the thalamus. MD is characterized by its robust interconnections with other brain areas, especially with limbic-related structures. Given the close anatomo-functional relationship between the MD and the limbic system, this particular thalamic nucleus can directly influence various affective behaviors and participate in cognition. In this work, we review data collected from multiple anatomical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 120 publications
(197 reference statements)
0
27
2
Order By: Relevance
“…Using tetrode recording in free-moving mice, Lee et al (2011) showed that the tonic firing frequency of MD neurons positively correlates with the extent of fear extinction. In addition, enhancing tonic firing of MD neurons facilitated fear extinction, whereas burst-evoking stimulation suppressed extinction, indicating that distinct firing modes of MD neurons might bidirectionally modulate salience of fear-associated cue ( Lee et al, 2011 ; Georgescu et al, 2020 ).…”
Section: Connectivity Profiles Of Thalamic Nucleimentioning
confidence: 98%
See 1 more Smart Citation
“…Using tetrode recording in free-moving mice, Lee et al (2011) showed that the tonic firing frequency of MD neurons positively correlates with the extent of fear extinction. In addition, enhancing tonic firing of MD neurons facilitated fear extinction, whereas burst-evoking stimulation suppressed extinction, indicating that distinct firing modes of MD neurons might bidirectionally modulate salience of fear-associated cue ( Lee et al, 2011 ; Georgescu et al, 2020 ).…”
Section: Connectivity Profiles Of Thalamic Nucleimentioning
confidence: 98%
“…Anatomically, the MD receives modulatory input from the midbrain and brainstem and forms a reciprocal connection with the frontal cortex ( Russchen et al, 1987 ; Mitchell, 2015 ; Collins et al, 2018 ). Single MD neurons receive convergence of small cortical inputs and project to multiple cortices across multiple layers ( Rubio-Garrido et al, 2009 ; Kuramoto et al, 2017 ; Georgescu et al, 2020 ). Schmitt et al (2017) proposed that the MD sustains rule representations in the PFC.…”
Section: Connectivity Profiles Of Thalamic Nucleimentioning
confidence: 99%
“…However, feedback projections from the PFC to the MD appear to mediate cognitive performance (Bolkan et al, 2017), and the MD may very well play a more active, continuous role than this view would imply. Furthermore, poly-synaptic feedback loops from the PFC to the striatum could also play a role, as the basal ganglia innervate the MD (Georgescu et al, 2020). Disconnection designs do not provide sufficient selectivity to dissociate these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…One promising candidate region is the mediodorsal nucleus (MD) of the thalamus. Neuroanatomically, the MD shares dense, reciprocal projections with the PFC across species (Alcaraz et al, 2016;Georgescu et al, 2020;Ray & Price, 1993). Functionally, the MD plays a role in cognitive functions (Markowitsch, 1982;Peräkylä et al, 2017), although finding a robust, cross-species behavioral assay to test its role in cognition has been difficult (Brito et al, 1982;Mitchell & Chakraborty, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This effect might occur due to the failure of several structures, such as the motor cortex, brainstem, and spinal cord, to exert proper inhibition of the movements. A decreased capacity of the globus pallidus to inhibit the thalamus can subsequently hyperactivate the medial and prefrontal cortical regions and decrease the activity in the primary motor cortex (41,42).…”
Section: Asymmetries In Focal Dystoniamentioning
confidence: 99%